East of Adelaide: Photographs of Commercial, Industrial and Working-class Urban Ontario, 1905-1930 - Pedersen, Diana (Labour / Le Travail, 1991)
The article reviews the book, "East of Adelaide: Photographs of Commercial, Industrial and Working-Class Urban Ontario 1905-1930," by Alan Noon.
Keywords: BOOKS -- Reviews; EAST of Adelaide: Photographs of Commercial, Industrial & Working-Class Urban Ontario 1905-1930 (Book); NOON, Alan; Nonfiction; Working class